ANALISIS KESULITAN BELAJAR IPA SISWA DI KELAS V SD NEGERI 046577 MUNT - Rupina Magdalena Br Tarigan (JURNAL TEMATIK, 2021)
This study aims to determine the ability of students in learning sound material in science subjects and students' learning difficulties in sound material in science subjects and the factors that cause student learning difficulties. This research was conducted in the fifth grade of SD Negeri 046577 Munte for the 2020/2021 academic year. The population of this study were students of class V and the sample of this study were all students of Class V, totaling 25 people. The instruments of this research are tests and interviews. Descriptive and qualitative data analysis techniques. Based on the results of the tests in the study, it was found that the students' ability to work on the sound material and their propagation average value of 63.2 was included in the criteria of underprivileged with difficulty working on question number 1, namely writing down the meaning of sound with a percentage of difficulty 60 (%) or included in the criteria. enough, in question number 2, which is to write down the meaning of the characteristics of sound with a difficulty percentage of 40 (%) or fall into the low criteria, in question number 3, which is to explain 5 causes of sound with a difficulty percentage of 64 (%) or enter into high criteria, in question number 4, which is to explain the propagation of sound through the medium of solids, liquids, and gases with a percentage of difficulty 72(%) or in the high criteria, in question number 5 explain why sound travels faster through solids with a percentage of 84(%) ) or fall into the very high criteria. The factors that cause student difficulties are students who do not understand the sound material and its propagation because they are not interested in learning it and never repeat the science lesson on sound material.